Economic valuation of marine protected areas: a review of studies in Southeast Asia - Akhter, Shammi (ARF Publication Sourcing, 2013)
Marine Protected Areas (MPAs) are key habitats for the conservation of important marine resources. However, most of the MPAs in the world are mismanaged. This paper provides a review of some of the valuation studies on marine protected areas in Southeast Asia. The purpose of this paper is to examine whether economic valuation provides valuable information to policy makers to mitigate the problems in marine protected areas in Southeast Asia. There are 17 studies related to marine protected areas in Southeast Asia that are discussed in this paper in order to determine their implications in policy decisions. Findings from these studies are inferred to maintain sustainable marine resource management in Southeast Asia. Results from this study suggest that more research is needed, as there are limited literatures on this important issue. Moreover, economic valuation is able to provide vital information in policy implications.